Whewell's tidal researches: scientific practice and philosophical methodology - Ducheyne, Steffen (Studies in History and Philosophy of Science Part A, 2010)
Primarily between 1833 and 1840, William Whewell attempted to accomplish what natural philosophers and scientists since at least Galileo had failed to do: to provide a systematic and broad-ranged study of the tides and to attempt to establish a general scientific theory of tidal phenomena. I document the close interaction between Whewells philosophy of science (especially his methodological views) and his scientific practice as a tidologist. I claim that the intertwinement between Whewells methodology and his tidology is more fundamental than has hitherto been documented.